RESOURCES FOR DEVELOPMENT OF THE RAČA MUNICIPALITY AS A RURAL TOURISM DESTINATION - Milićević, Snežana; Podovac, Milena; Čavlin, Miroslav (Economics of Agriculture, 2015)
The attractiveness of rural areas is the basis for development of tourist offer of rural tourism destination. Bearing in mind that the villages are ecologically and environmentally preserved integrities, it is a sustainable form of tourism, which contributes to the development of rural economy. Villages that foster traditional values are of attractive tourist destinations. Staying of tourists in the villages enables active involvement of other economic activities in the creation of the integrated tourism product. Tourism of the Rača Municipality, despite the existence of attractive resources, is not adequately developed. Tourist offer is of amodest scale and based on the sites of cultural and historical heritage and events. The development of tourism in this municipality requires institutional support of local government, investments and cooperation of holders of the tourism offer. In this paper, the emphasis is on the analysis of the current situation of tourism development in the municipality of Rača, with emphasis on resources for the development of rural tourism. Based on examples of good practice - rural tourism destinations in Europe and Serbia, the contribution of labor is reflected in providing guidelines for the future development of rural tourism in Rača.